Getting started with advanced C# : upgrade your programming skills - Sarcar, Vaskaran (Apress, 2020)
Understand and work with the most important features of advanced C# in different programming environments. This book teaches you the fundamental features of advanced C# and how to incorporate them in different programming techniques using Visual Studio 2019. The book is divided into two parts. Part I covers the fundamentals and essentials of advanced programming in C#. You will be introduced to delegates and events and then move on to lambda expressions. Part II teaches you how to implement these features in different programming techniques, starting with generic programming. After that, you will learn about thread programming and asynchronous programming, to benefit from a multi-threaded environment. Finally, you will learn database programming using ADO.NET to connect to a MySQL database and you will know how to exercise SQL statements and stored procedures through your C# applications. You will: Use delegates, events, and lambda expressions in advanced programming Make your application flexible by utilizing generics Create a fast application with multi-threading and asynchronous programming Work in Visual Studio Community Edition, which is the most common IDE for using C# Understand alternative implementations along with their pros and cons.